An updated report on the incidence and epidemiological trends of keratinocyte cancers in the United Kingdom 2013–2018. Issue 4 (18th August 2021) - Kwiatkowska, M.; Ahmed, S.; Ardern‐Jones, M.; Bhatti, L. A.; Bleiker, T. O.; Gavin, A.; Hussain, S.; Huws, D. W.; Irvine, L.; Langan, S. M.; Millington, G. W. M.; Mitchell, H.; et al.
Abstract: Introduction: The most common cancers in the UK are keratinocyte cancers (KCs): the combined term for basal cell carcinomas (BCCs) and cutaneous squamous cell carcinomas (cSCCs). Registration of KC is challenging due to high numbers and multiplicity of tumours per person. Methods: We provide an updated report on the descriptive epidemiology of trends in KC incidence for the resident populations of UK countries (England, Northern Ireland, Scotland and Wales) using population‐based cancer registry and pathology report data, 2013–18. Results: Substantial increases in cSCC incidence in England, Scotland and Northern Ireland can be detected for the period of 2013–18, and the incidence of cSCC also increased in Wales from 2016 to 2018. In contrast, however, the pattern of annual change in the incidence of BCC across the nations differs. In England, the incidence of BCC declined slightly from 2016 to 2018, however, the overall trend across 2013–18 is not statistically significant. In Scotland, the incidence of BCC shows some variability, declining in 2017 before increasing in 2018, and the overall trend across 2013–18 was also not statistically significant. In Northern Ireland, the incidence of BCC increased significantly over the study period, and in Wales, the incidence of BCC increased from 2016 to 2018. One in five people will develop non‐melanoma skin cancers (NMSC) in their lifetime in England. This estimate is much higher than the lifetime risk of melanoma (1 in 36 males and 1 in 47 females born after 1960 in the UK), which further highlights the burden of the disease and importance of early prevention strategies. Conclusions: We highlight how common these tumours are by publishing the first ever lifetime incidence of NMSC. Additionally, the first time reporting of the age standardised incidence of KC in Wales further confirms the scale of the disease burden posed by these cancers in the UK. With approximately one in five people developing NMSC in their lifetime, optimisation of skin cancer prevention, management and research are essential. Abstract : The commonest skin cancers are keratinocyte cancers (KCs), the combined term for basal cell carcinomas (BCC) and cutaneous squamous cell carcinomas (cSCC). We provide an updated report on KC incidence and epidemiological trends in the United Kingdom using data from national cancer registries in England, Scotland, Northern Ireland and Wales in 2013‐18. We highlight how common these tumours are by publishing the first ever lifetime incidence of NMSC, which indicates that one in five people in England will develop a NMSC at some point in their lifetime.